Utilization of GPT Chat for the Development of Linguistics - Amanda, Sharina (Universitas Syiah Kuala, 2023)
The development of artificial intelligence technology has made a significant contribution in various fields, including linguistics. One of the latest developments is the use of a GPT (Generative Pre-trained Transformer) based language model in chatbot applications. This journal article conducts a literature review on the use of GPT Chat for the development of linguistics. Through analysis of the literature, this article describes how the application of GPT Chat in language applications contributes to human language understanding, language analysis, and the development of linguistics as a whole.